Historical exposure to persistent organic pollutants and cardiovascular disease: A 15-year longitudinal analysis focused on pharmaceutical consumption in primary care - Perez-Carrascosa, Francisco M; Gómez-Peña, Celia; Echeverría, Ruth; Jiménez-Moleón, José Juan; Melchor, Juan M; García-Ruiz, Antonio J.; Navarro-Espigares, José Luis; Cabeza Barrera, Jose; Martin-Olmedo, Piedad; Ortigosa-García, Juan Carlos; Arrebola, Juan Pedro (Elsevier, 2021)
Objectives: To explore the potential contribution of historical POP exposure to 15-year pharmaceutical consumption in relation to CVD. Methods: This study is framed within GraMo adult cohort. Participants (n = 387) were recruited in two hospitals in Granada province, Southern Spain (2003–2004). Historical exposure to 5 OCPs and 3 non-dioxine-like PCBs was estimated by analysing adipose tissue concentrations at recruitment. Pharmaceutical consumption from recruitment until year 2017 was quantified by reviewing dispensation databases. Average consumption increase (ACI) in CVD medication was calculated by subtracting average consumption in 2002 to the average yearly consumption during follow-up. ACI was expressed as Defined Daily Dose (DDD)/year units. Data analyses were carried out using a multivariable multinomial logistic regression and weighted quantile sum regression (WQS), with ACI categorized in quartiles (Q) as the dependent variable. Results: Concentrations of most pollutants showed a positive trend with the quartiles of ACI. Particularly, PCB- 153 showed increasing and statistically significant odds ratios (ORs) for Q2 (OR: 1.27, 95% confidence interval (CI): 1.07–1.52), Q3 (OR: 1.49, 95 %CI: 1.17–1.88) and Q4 (OR: 1.42, 95 %CI: 1.13–1.78) vs Q1. Similarly, beta-hexachlorocyclohexane (β-HCH) also showed increasing ORs, that reached statistical significance in Q4 (OR: 1.36, 95 %CI: 1.06–1.74) vs Q1. These findings were corroborated by WQS analyses, that revealed a significant mixture effect, predominantly accounted for by PCB-153 and β-HCH.
CC BY-NC-ND
Keywords: Sistema cardiovascular - Enfermedades; Sistema cardiovascular - Efectos de los medicamentos; Organochlorine pesticides; Polychlorinated biphenyls; Persistent Organic Pollutants; Cardiovascular disease; Pharmaceutical consumption; Health expenditure